Implementasi Akad Mudharabah pada Produk Simpanan Hewan Qurban - Abdilah, Ulil Absor Faiq; Mustofa, Mustofa; Ilmiyah, Izzatul (Journal of Industrial and Syariah Economics, 2025)
Although conceptually, the mudharabah contract emphasizes business cooperation between the fund owner (shahibul maal) and the fund manager (mudharib), in practice, there are still discrepancies between theory and its implementation in the field. This study aims to analyze the implementation of the mudharabah contract in the SiMudaQu product and to assess its level of compliance with Sharia principles and the DSN-MUI fatwa. The research methodology used in this study is descriptive qualitative research with a field research approach. Data collection techniques were employed through in-depth interviews, direct observation, and documentation studies involving BMT managers and members who utilize the SiMudaQu product. The data obtained were analyzed using a descriptive qualitative analysis method by comparing the practices in the field with the theory of fiqh muamalah and the provisions contained in DSN-MUI Fatwa No. 07/DSN-MUI/IV/2000 concerning Mudharabah (Qiradh) Financing. The results show that the implementation of the mudharabah contract in the SiMudaQu product is not fully in accordance with the theory of fiqh muamalah. Administratively, the BMT has used the mudharabah contract through the signing of documents and the establishment of a ratio of 40% for members and 60% for the BMT. However, the savings funds are not managed productively, as is characteristic of a true mudharabah. This practice indicates that the contract used is still formal and administrative in nature and does not reflect the principles of partnership and justice as stipulated in the DSN-MUI fatwa No. 07/DSN-MUI/IV/2000. Therefore, a review of the application of the contract in the SiMudaQu product is necessary to ensure its compliance with sharia principles and the values ​​of maqāṣid al-syarī‘ah.